Consequences of point mutations in melanoma-associated antigen 4 (MAGE-A4) protein: Insights from structural and biophysical studies. - Hagiwara,Y; Sieverling,L; Hanif,F; Anton,J; Dickinson,ER; Bui,TTT; Andreeva,A; Barran,PE; Cota,Segura E; Nikolova,PV (Scientific Reports, 2016)
The Melanoma-Associated Antigen A4 (MAGE-A4) protein is a target for cancer therapy. The function of this protein is not well understood. We report the first comprehensive study on key cancer-associated MAGE-A4 mutations and provide analysis on the consequences of these mutations on the structure, folding and stability of the protein. Based on Nuclear Magnetic Resonance and Circular Dichroism, these mutations had no significant effects on the structure and the folding of the protein. Some mutations affected the thermal stability of the protein remarkably. Native mass spectrometry of wild-type MAGE-A4 showed a broad charge state distribution suggestive of a structurally dynamic protein. Significant intensity was found in relatively low charge states, indicative of a predominantly globular form and some population in more extended states. The latter is supported by Ion Mobility measurements. The MAGE-A4 mutants exhibited similar features. These novel molecular insights shed further light on better understanding of these proteins, which are implicated in a wide range of human cancers.